(untitled) (Medical Forum Monthly, 2026)
Objective: To investigate the therapeutic effects of acarbose alone and in combination with thymol on oxidative stress, β-cell function, and glycemic control in streptozotocin (STZ)-induced diabetic rats. Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the College of Science at Babylon University, Iraq from 15th July 2025 to 14th December 2025. Methods: Forty male albino rats (180–320 g) were maintained under controlled conditions (22–25°C, 50% humidity, free access to water). After 2 weeks, rats were randomly divided into four groups: negative (A), positive (B), acarbose-treated (C), and acarbose plus thymol-treated (D). After treatment, rats were sacrificed and blood samples were collected for biochemical and inflammatory analyses. Results: Group B showed decreased superoxide dismutase (0.337±0.091) and C-peptide (863.17±250.14), with increased advanced oxidation protein products (430.37±77.85) and glucose (148±29.71) vs A (p<0.05). Group C increased superoxide dismutase (0.554±0.155) and C-peptide (1248.78±303.68) and reduced advanced oxidation protein products (271.42±120.38) and glucose (102.9±12.74) (p<0.05). Group D further increased superoxide dismutase (0.615±0.202) and C-peptide (1368.33±277.35) and decreased advanced oxidation protein products (269.74±59.11) and glucose (97±7.46) (p<0.05). Conclusion: Acarbose improves oxidative stress and glycemic status, while thymol provides additionalimprovement.